The Development of Critical Care Medicine in China: From SARS to COVID-19 Pandemic - Haiyan Yin; Shan Wang; Youfeng Zhu; Rui Zhang; Xiaoling Ye; Jianrui Wei; Peter C. Hou (Critical Care Research and Practice)
Background. Critical care medicine is a branch of medical science that deals with the characteristics and regularity of life-threatening processes initiated by any injury or disease and, accordingly, relevant treatment for patients with critical illness. Conceptions of critical care medicine in China stemmed in the early 1970s. Ever since the establishment of the first intensive care unit (ICU) along with the increasingly incomparable role of ICU in medical practices, critical care medicine has become an indispensable part of the Chinese medical and health system. Currently, critical care medicine as a secondary clinical discipline and a well-constructed science is in sustainable development on the way towards systematization and standardization. Methods. The gross domestic product (GDP) and population data were obtained from the National Bureau of Statistics. The number of ICUs, ICU beds, and hospital beds and other data regarding ICU staffing and facility resources were obtained from the Yearbook of Health in the People’s Republic of China and National Bureau of Statistics. The mortality rates of SARS and COVID-19 and the number of health workers aiding Hubei amid COVID-19 pandemic were obtained from the National Health Commission. Findings. Critical care medicine in mainland China has made significant strides: both quantity and quality are progressing at a fast pace after SARS in 2003. Although there exist some disparities in healthcare personnel and medical resources, they have not hindered the country from mobilizing its healthcare workers and resources against a public health emergency.